2013
DOI: 10.1103/physrevb.87.081101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy in hole-doped superconducting Ba0.67K0.33Fe2

Abstract: We use polarized inelastic neutron scattering (INS) to study spin excitations of optimally holedoped superconductor Ba0.67K0.33Fe2As2 (Tc = 38 K). In the normal state, the imaginary part of the dynamic susceptibility, χ ′′ (Q, ω), shows magnetic anisotropy for energies below ∼7 meV with c-axis polarized spin excitations larger than that of the in-plane component. Upon entering into the superconducting state, previous unpolarized INS experiments have shown that spin gaps at ∼5 and 0.75 meV open at wave vectors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…It is noteworthy that anisotropic fluctuations typically appear above T c [Figs. 7(c) and 7(e)], and develop into an anisotropic resonance mode or become partially gapped inside the superconducting state [34][35][36][37]42,52]. BaFe 2 As 1.4 P 0.6 appears to be an exception, with anisotropic spin fluctuations only present in the superconducting state [44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that anisotropic fluctuations typically appear above T c [Figs. 7(c) and 7(e)], and develop into an anisotropic resonance mode or become partially gapped inside the superconducting state [34][35][36][37]42,52]. BaFe 2 As 1.4 P 0.6 appears to be an exception, with anisotropic spin fluctuations only present in the superconducting state [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the normal state [ Fig. 4(d)], spin anisotropy is also observed, similar to electron-and hole-doped BaFe 2 As 2 [36,37,52], but different from isovalently doped BaFe 2 As 1.4 P 0.6 [44].…”
Section: B Polarization Of Spin Fluctuations From Polarized Neutron mentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate the relevance of SOC to superconductivity, it is instructive to compare the behavior of the spin anisotropy in hole-doped and electron-doped BaFe 2 As 2 , since the maximum values of T c are quite different in these two cases -T c ≈ 38 K for optimally hole-doped Ba 0.67 K 0.33 Fe 2 As 2 and T c ≈ 25 K for optimally electron-doped BaFe 1.86 Co 0.14 As 2 . Previous analysis of the electron-doped case revealed that the spin anisotropy persists in the paramagnetic tetragonal phase for doping levels up to or slightly beyond optimal doping [34][35][36][37][38][39] , but vanishes in the well-overdoped regime 38,40 . In this paper, we present polarized neutron scattering studies of spin excitations in optimally hole-doped Ba 0.67 K 0.33 Fe 2 As 2 17,37 .…”
Section: Introductionmentioning
confidence: 99%